Transforming from victim to survivor—Part 2: Fixing the systems that enable disruptive intraoperative behaviour - Forest, Alison; Adams, Brett; Krestow, Owen; Yasinski, Lesia; Villafranca, Alexander (Operating Room Nurses Association of Canada Journal, 2025)
Disruptive intraoperative behaviour is prevalent and consequential. It undermines patient care, sets a poor example for medical students, and erodes clinician wellbeing. Part 1 of this article series emphasized the importance of micro-level solutions, including proper appraisals and behavioural responses by victims and witnesses. However, focusing exclusively on clinician-level strategies puts undue responsibility on those individuals already affected. Part 2 focuses on the broader systems that allow disruptive behaviour to persist and, more importantly, how they can be changed. Specifically, this article explores how systems of hiring, education, mentorship, and cultural reinforcement shape the clinical environment and can either enable or prevent unprofessional conduct. Hiring practices should include candid discussions about professional expectations and anticipated challenges, while selecting candidates aligned with organizational values. Educational programs should explicitly teach clinicians the values and soft skills needed to avoid and mitigate disruptive behaviour and then engrain these skills using simulation. Mentorship systems should match new clinicians with good models of professionalism and should leverage advancements in professionalism education to hasten cultural change. Finally, organizations should create clear policies, enforce behavioural expectations consistently and fairly, create confidential reporting mechanisms, adjust working conditions to reduce stress and burnout, and supply supports to clinicians in need. Complex social issues like disruptive behaviour require both individual action and systems reform. Ultimately, combining these micro and macro-level solutions can mitigate the negative impacts of disruptive behaviour and shift organizational culture toward professionalism and safety.